Conversations with form : a workbook for students of architecture - Habraken, N. J.; Mignucci Giannoni, Andres; Teicher, Jonathan (New York : Routledge, Taylor & Francis Group, 2014)
'Through a progressive series of exercises - accompanied by observational studies, examples and applied theory - Conversations with Form: A Workbook for Students of Architecture improves designers' understanding, dexterity and resilience in making form. It specifically focuses on the skills needed to succeed in the everyday context in which the vast majority of architects will ultimately design and build, wherein no one designs in isolation and existing conditions never represent a tabula rasa. The text begins by familiarizing readers with utilizing step-by-step sequences of moves to steer the development of built form and rapidly moves to designs of increasing complexity. These design plays treat a wide-ranging series of topics including structures, patterns, types, systems and other kinds of shared form principles. Conversations with Form is a workbook for honing hands-on skills and tools of the architect's trade. Beautifully illustrated and focused on practical, usable information, the book provides architectural students with an accessible and useable handbook for their design practice'--
Includes bibliographical references (pages 239-242) and index.
Keywords: Architectural design -- Problems, exercises, etc; Architecture -- Composition, proportion, etc